2014
DOI: 10.1186/1470-7330-14-22
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging features of intracranial primary CNS lymphoma in immune competent patients

Abstract: We aimed to characterize specific MRI findings seen in immune competent patients with intracranial primary CNS lymphoma (PCNSL) and to determine their value in the management of such patients. Pre-treatment MRI examinations of 21 immunocompetent patients with biopsy-proven PCNSL were retrospectively evaluated. T1 and T2 signal characteristics as well as contrast enhancement features are described in all patients. Diffusion, perfusion and proton-MR-spectroscopy features are described in a subset of these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 20 publications
5
54
0
Order By: Relevance
“…NAA is predominantly located in neurons and is thus decreased in all neoplasms that cause neurons to be displaced or replaced with malignant cells. 29 Numerous studies have demonstrated decreased NAA peak, mainly in glial neoplasms 30 and primary CNS lymphoma, 31 consistent with our results. Our results also suggest that APT mean indirectly reflects neuronal loss due to brain tumor infiltration.…”
Section: Discussionsupporting
confidence: 92%
“…NAA is predominantly located in neurons and is thus decreased in all neoplasms that cause neurons to be displaced or replaced with malignant cells. 29 Numerous studies have demonstrated decreased NAA peak, mainly in glial neoplasms 30 and primary CNS lymphoma, 31 consistent with our results. Our results also suggest that APT mean indirectly reflects neuronal loss due to brain tumor infiltration.…”
Section: Discussionsupporting
confidence: 92%
“…5,6 The unique features of our patient are that she did not have classic MRI findings of a PCNSL but later evolved to classic MRI findings with T1 and T2 FLAIR hyperintesities with homogenous contrast enhancement. 13 Also, her CSF cytology and flow cytometry was negative for lymphoma, but her 14-3-3 protein was elevated with Creutzfeldt-Jakob disease in the differential diagnosis. 14-3-3 protein is found in neuronal cytoplasm, glia, and synaptic membranes of the brain.…”
Section: Discussionmentioning
confidence: 97%
“…On routine MRI, low grade gliomas are typically non-enhancing 11 while lymphomas typically demonstrate homogeneous enhancement and restricted diffusion on diffusion-weighted imaging. 12 Pattern of contrast enhancement may be another useful tool in identifying a TDL. In this study, all TDLs demonstrated incomplete ring-enhancement while this pattern did not occur among the HGG group.…”
Section: Discussionmentioning
confidence: 99%